A Gelatin Methacrylate-Based Hydrogel as a Potential Bioink for 3D Bioprinting and Neuronal Differentiation - Elisa Marozzi Cruz; Lucas Simões Machado; Laura Nicoleti Zamproni; Larissa Valdemarin Bim; Paula Scanavez Ferreira; Leonardo Alves Pinto; Luiz Antonio Pessan; Eduardo Henrique Backes; Marimélia Aparecida Porcionatto (MDPI AG, 2023)
Neuronal loss is the ultimate pathophysiologic event in central nervous system (CNS) diseases and replacing these neurons is one of the most significant challenges in regenerative medicine. Providing a suitable microenvironment for new neuron engraftment, proliferation, and synapse formation is a primary goal for 3D bioprinting. Among the various biomaterials, gelatin methacrylate (GelMA) stands out due to its Arg-Gly-Asp (RGD) domains, which assure its biocompatibility and degradation under physiological conditions. This work aimed to produce different GelMA-based bioink compositions, verify their mechanical and biological properties, and evaluate their ability to support neurogenesis. We evaluated four different GelMA-based bioink compositions; however, when it came to their biological properties, incorporating extracellular matrix components, such as GeltrexTM, was essential to ensure human neuroprogenitor cell viability. Finally, GeltrexTM: 8% GelMA (1:1) bioink efficiently maintained human neuroprogenitor cell stemness and supported neuronal differentiation. Interestingly, this bioink composition provides a suitable environment for murine astrocytes to de-differentiate into neural stem cells and give rise to MAP2-positive cells.